Tradisi Adat "ACCERA KALOMPOANG" di Balla Lompoa Gowa Sebagai Warisan Budaya Kerajaan Gowa - Nasya Diva Aprilia R.G; Siska Febrianti; Haniah Haniah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
Accera Kalompoang is a royal ceremonial tradition held at Balla Lompoa, Gowa, South Sulawesi, as a form of respect toward the sacred royal heirlooms (kalompoang) of the Kingdom of Gowa. The ritual reflects historical memory, political legitimacy, and spiritual beliefs inherited from the Gowa kingdom era and preserved by the local community. This study aims to analyze the historical background, ritual procession, symbolic meanings, socio-religious functions, and the dynamics of preservation of the Accera Kalompoang tradition. The research uses a qualitative descriptive approach through literature review and analysis of previous ethnographic studies and cultural documentation. The findings show that Accera Kalompoang functions not only as a ceremonial cleansing of royal heirlooms but also as a medium of collective identity, cultural continuity, and social integration between traditional authorities and society. Despite modernization and changing social structures, the tradition continues to be maintained as a symbol of historical legitimacy and cultural pride of the Gowa people. Therefore, Accera Kalompoang represents a living heritage that adapts to contemporary contexts while preserving the values of the Gowa Kingdom’s cultural legacy.